A mechanistic insight into glucose conversion in subcritical water: Complex reaction network and the effects of acid-base catalysis. (1st April 2021) - Yan, Zhifeng; Lian, Jie; Feng, Yu; Li, Miaoting; Long, Feng; Cheng, Ruoqian; Shi, Sheng; Guo, Hong; Lu, Jianjun
Graphical abstract: Highlights: A product-oriented reaction network of glucose conversion is given by DFT-D approach. O(5) site of glucose has the most highest reactivity to be protonated in sub-CW. H + may be responsible for isomerization and retro -aldol condensation in sub-CW. The results reasonably explain activity and selectivity for glucose and fructose. Thermodynamic results explain product distribution over temperature in sub-CW. Abstract: Based on the concept of system thinking and system design, a systematically mechanistic network of glucose conversion toward fructose, 5-hydroxymethyl furfural, 1, 6-anhydroglucose, 1, 2, 4-Benzenetriol, levulinic acid, furfural, erythrose, glyceraldehyde, dihydroxyacetone, pyruvaldehyde, lactic acid, glycolaldehyde in subcritical water were performed by employing dispersion-corrected density functional theory. Fukui functions results predict the most highest reactivity of O(5) of glucose to suffer protonation in subcritical water, which may readily lead to the formation of 1, 6-anhydroglucose or fructose with the comparable apparent activation energies (29.441 vs 29.305 kcal/mol). Further dehydration of monosaccharide to 5-HMF is more favorable via cyclic pathway for fructose in comparison to the acyclic pathway for glucose. The formation of levulinic acid has an apparent activation energy of 33.321 kcal/mol but the rate is limited by the numerous steps. The consumption of 5-HMF to 1, 2, 4-Benzenetriol exhibits a high activation energy of 76.682 kcal/mol. Retro-aldol condensation of C4 compounds prefer to give C2 rather than C3 compounds. The thermodynamic results involving the generation of C2, C3 and C4 compounds by retro -aldol condensation of open-chain C6 intermediates agree with the experimental product distribution and reactivity over temperature at the initial stage of glucose or fructose subcritical hydrolysis. Furthermore, the assistance of H + may be responsible for the isomerization and retro -aldol condensation in glucose conversion. This comprehensive reaction network provides a fundamental understanding and deeper insight into glucose conversion, which reasonably explains experimental activity and selectivity reported for glucose and fructose conversion in subcritical water.